The effectiveness of the Al-Kuliyyah television program in Islamic educational communication and its influence on Muslim lifestyles in Malaysia - Mohamad Kamal, Rusydi; Ibrahim, Noor Afzaliza Nazira; Jamri, Mohamad Hafifi; Sultan Mohideen, Rosilawati; Samar, Amir Nor Azan; Sah Allam, Siti Nur Shahidah (Faculty of Communication & Media Studies, 2025)
Media plays a crucial role in shaping public understanding, particularly in religious education. Television, as a mass communication tool, influences audiences through informative and engaging content. This study examines the effectiveness of the Al-Kuliyyah television program in delivering Islamic educational communication and guiding Muslim lifestyles in Malaysia. Using a mixed-methods approach, including surveys, interviews, and audience analysis, the research evaluates the program’s impact on viewers' religious knowledge, attitudes, and practices. Findings suggest that Al-Kuliyyah enhances Islamic awareness, fosters moral values, and influences personal and social behavior. However, media competition, audience engagement, and digital transformation remain key challenges. The study highlights the significance of religious broadcasting and proposes strategies for improving its effectiveness in contemporary media landscapes, including content diversification, digital engagement, and audience-centered programming.